Polymorphism of the Platelet Glycoprotein IIIa Gene in Patients with Coronary Stenosis - Garcia-Ribes, Miguel; Gonzalez-Lamuño, Domingo; Hernandez-Estefania, Rafael; Colman, Thierry; Pocovi, Miguel; Delgado-Rodriguez, Miguel; Garcia-Fuentes, Miguel; Revuelta, Jose M. (Thrombosis and Haemostasis, 1998)
Based on genetic variability, structural differences in the glycoprotein IIb/IIIa platelet receptor for adhesive proteins result in individual differences in the thrombogenicity of platelets. Recent studies suggest a controversial association between a genetic polymorphism of the glycoprotein IIIa gene (PlA2) and the risk of coronary artery disease. In our study, the prevalence of the PlA2 allele in a group of patients undergoing percutaneous coronary revascularization was 37%, a value significantly higher than in controls [13%, odds ratio (OR) = 3.93, 95% CI, 1.84 to 8.53] suggesting a significant association between this polymorphism and documented coronary stenosis, which is strongest among <60 years old patients (OR = 12.30, 95% CI, 2.98 to 70.93). This polymorphism represents an inherited risk factor for severe cardiovascular disease due to coronary occlusion.